2018
DOI: 10.1111/1475-4932.12440
|View full text |Cite
|
Sign up to set email alerts
|

Childcare Use and Its Role in Indigenous Child Development: Evidence from the Longitudinal Study of Indigenous Children in Australia

Abstract: We investigate patterns of childcare use and its influence on the cognitive development of Indigenous children. The influence of childcare on Indigenous children's cognitive outcomes is less well understood than for non‐Indigenous children due to a lack of appropriate data. We focus on a cohort of Indigenous children in Australia who have been followed from infancy and for whom rich information on childcare use and cognitive outcomes is observed. Compared to Indigenous children who never participated in childc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…A previous study of <1000 Indigenous children in the LSIC also found a generally positive association with preschool, but mixed findings with long daycare centres, after controlling for available confounders. 14 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study of <1000 Indigenous children in the LSIC also found a generally positive association with preschool, but mixed findings with long daycare centres, after controlling for available confounders. 14 15…”
Section: Discussionmentioning
confidence: 99%
“…Among approximately 1000 children in the Longitudinal Study of Indigenous Children, preschool and childcare attendance were associated with positive cognitive and developmental outcomes, after adjusting for confounders. 14 15 Longer hours of childcare were negatively associated with child outcomes in studies of both Indigenous and non-Indigenous Australian children; however, this was not the case for preschool. 14 16…”
Section: Introductionmentioning
confidence: 94%
“…Evidence suggests that childcare choice plays a vital role in maternal labour force participation (Boll & Lagemann, 2019), and there is a strong link between childcare and children's outcomes (Grogan, 2012;Azpitarte et al, 2016). Therefore, investigating parental childcare choosing has been a continuing concern of academics, especially in Anglophone countries where a marketised approach is applied, notably the UK, the USA, New Zealand, Canada and Australia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using the Longitudinal Survey of Indigenous Children (LSIC) and the Longitudinal Survey of Australian Children (LSAC), the difference in formal childcare attendance between the general population of children and the population of Indigenous children is substantial. Based on the LSIC, Azpitarte et al () find that no more than 30 per cent of Indigenous children attend childcare at any given age, while based on the LSAC, Houng, Jeon and Kalb () report that 55 per cent of the general population of children aged 2–3 use formal childcare. Examining the same LSAC sample, Kalb, Tabasso and Zakirova (2014) report that children in families on low and middle incomes (under $73,000) and children in families where only one of the parents is employed are the least likely to attend any formal childcare.…”
Section: Participation In Childcare and Preschool In Australiamentioning
confidence: 99%
“…For example, despite the substantially lower overall formal childcare use by Indigenous families, usage varies according to parental employment similar to the variation in non‐Indigenous groups. Differences by parental education level are even much larger for Indigenous children than for children in the general population (Houng, Jeon and Kalb 2011; Azpitarte et al ).…”
Section: Participation In Childcare and Preschool In Australiamentioning
confidence: 99%